2010
DOI: 10.1029/2009jd012864
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of strong absorbers and fluorophores in limonene‐O3 secondary organic aerosol due to NH4+‐mediated chemical aging over long time scales

Abstract: [1] This study investigated long-term chemical aging of model biogenic secondary organic aerosol (SOA) prepared from the ozonolysis of terpenes. Techniques including electrospray ionization mass spectrometry (ESI-MS), UV-visible spectroscopy, Fourier transform infrared (FTIR) spectroscopy, NMR, and three-dimensional fluorescence were used to probe the changes in chemical composition of SOA collected by impaction on substrates and also of aqueous extracts of SOA. The addition of ammonium ions or amino acids to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
366
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 281 publications
(387 citation statements)
references
References 97 publications
20
366
1
Order By: Relevance
“…stages of aqueous aging, which is obscured by the 500 nm band at longer timescales and upon evaporation. 26,35 Even this temporal evolution of chromophores in limonene/O 3 SOA can be reproduced by KLA (Fig. S4 in the ESI section †), offering strong evidence of similar chemistry.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…stages of aqueous aging, which is obscured by the 500 nm band at longer timescales and upon evaporation. 26,35 Even this temporal evolution of chromophores in limonene/O 3 SOA can be reproduced by KLA (Fig. S4 in the ESI section †), offering strong evidence of similar chemistry.…”
Section: Resultsmentioning
confidence: 87%
“…25,26 Interestingly, SOA components generated from the ozonolysis of apinene, an isomeric monoterpene, do not form brown carbon when reacted with the same nitrogen species. 26,27 Both limonene and a-pinene are abundant volatile organic compounds, so it is important to understand their potential to modify aerosol optical properties. For example, limonene and a-pinene contribute 3-18% and 23-53%, respectively, to the total monoterpene emissions from forests in the United States.…”
Section: -24mentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Bones et al [11], with the aim to investigate chemical aging of SOA formed from ozonolysis of terpenes in the presence of ammonium sulfate aerosol, FTIR was used to confirm whether the "colored" products, which showed strong visible absorption measured by UV-Vis spectroscopy and fluorescence at UV and visible ranges by three-dimensional fluorescence, could lead to the changes in the chemical compositions of SOA. By comparing FTIR spectra of the fresh SOA to those of the chemically aged SOA, almost no difference was observed, which implied that the "colored" products from the long-term aging chemistry contributed insignificantly to the aged SOA.…”
Section: Aerosol Research By Ftir Spectroscopymentioning
confidence: 99%
“…Although careful work has suggested that organo-nitrogen species are largely responsible for the bulk absorptivity of these amine-aldehyde systems (Bones et al, 2010), only a handful of aqBrC chromophores have been positively identified (Kampf 25 et al, 2012;Nguyen et al, 2012;Laskin et al, 2014;Lin et al, 2015;Aiona et al, 2017a). Most of these are functionalized and conjugated imidazole products, summarized in detail in a recent review (Laskin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%